Antología / Miguel de Unamuno ; prólogo de José Luis L . Aranguren ; [portada de Vicente Rojo] - Aranguren, José Luis L. (1909-1996) Rojo, Vicente; Unamuno, Miguel de (1864-1936) (Popular; 62)
Bibliografía: p. 386-392